2004
DOI: 10.1002/jgm.610
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic peptide containing loop 4 of nerve growth factor for targeted gene delivery

Abstract: The chimeric peptide reported will be useful in gene delivery to and gene therapy of the nervous system and other tissues/organs with cells expressing TrkA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Several strategies have been employed to overcome this challenge in the non‐viral gene delivery field, one of which is to utilize materials that specifically recognize neurons. Neuron‐specific toxin fragments, neurotransmitters and nerve growth factors have been employed as mediators of neuron recognition 13, 14, 16, 31. In this study, two materials, Tet1‐PEI and NT‐PEI, are evaluated for neuron‐specific gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been employed to overcome this challenge in the non‐viral gene delivery field, one of which is to utilize materials that specifically recognize neurons. Neuron‐specific toxin fragments, neurotransmitters and nerve growth factors have been employed as mediators of neuron recognition 13, 14, 16, 31. In this study, two materials, Tet1‐PEI and NT‐PEI, are evaluated for neuron‐specific gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, gene delivery to the CNS using nonviral vectors has not been successful due to the low transfection efficiencies achieved in non-dividing cells and low cellular uptake rates in terminally-differentiated neurons [88-90]. One approach to increase efficacy is to conjugate targeting ligands to polymeric vectors to enhance uptake by neuronal subtypes [7,91,92]. We previously demonstrated that conjugation of Tet1, a 12-mer peptide identified by in vitro phage display to bind the Gtb1 ganglioside [93], to polyethylenimine (PEI) enhanced gene delivery to neural progenitor cells (NPCs) [94].…”
Section: Design Of Peptide-based Polymersmentioning
confidence: 99%
“…Many peptides have been described in the literature as receptor-specific ligands so any of them can be added to the multifunctional proteins in order to confer them cell specificity. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The most natural specific ligands that can also be used for cell targeting are monoclonal antibodies. 32,[63][64][65] In addition, if no specific peptides are available for an intended target, new specific binding peptides can be found by using phage display 66 or combinatorial chemistry.…”
Section: Cell Binding and Internalizationmentioning
confidence: 99%